Metal fused filament fabrication of the nickel-base superalloy IN 718 - Thompson, Yvonne; Zissel, Kai; Förner, Andreas; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Neumeier, Steffen; Felfer, Peter (Journal of Materials Science, 2022)
This study demonstrates metal fused filament fabrication (MF3) as an alternative additive and highly flexible manufacturing method for free-form fabrication of high-performance alloys. This novel processing, which is similar to Metal injection molding (MIM), enables a significant reduction in manufacturing costs for complex geometries, since expensive machining can be avoided. Utilizing existing equipment and reducing material expense, MF3 can pave the way for new and low-cost applications of IN 718, which were previously limited by high manufacturing costs. Iterative process optimization is used to find the most suitable MF3 process parameters. High relative density above 97% after pressureless sintering can be achieved if temperature profiles and atmospheres are well adjusted for thermal debinding and sintering. In this study, the influence of processing parameters on the resulting microstructure of MF3 IN 718 is investigated. Samples sintered in vacuum show coarse-grained microstructure with an area fraction of 0.36% NbC at grain boundaries. Morphology and composition of formed precipitates are analyzed using transmission electron microscopy and atom probe tomography. The gamma/gamma ''/gamma' phases' characteristics for IN 718 were identified. Conventional heat treatment is applied for further tailoring of mechanical properties like hardness, toughness and creep behavior. Fabricated samples achieve mechanical properties similar to MIM IN 718 presented in literature.
CRIS-Team WoS Importer:2022-02-11